1997
DOI: 10.1111/j.1528-1157.1997.tb01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the Effect of Side of Seizure Onset on Recognition Memory Following Intracarotid Amobarbital Injection

Abstract: Summary:Purpose: To assess interhemispheric differences in recognition memory for objects during the intracarotid amobarbital sodium procedure (IAP).Methods: The recognition memory for real objects of patients with either right (RTLE, n = 28) or left (LTLE; n = 22) temporal lobe epilepsy was assessed at baseline, and after left and right intracarotid amobarbital sodium injection.Results: There were no differences between groups on baseline performance. Performance following injection ipsilateral to the side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To assess laterality for language during this procedure, patients were given tests of reading, naming, repetition, and comprehension (in the form of a modified token test) after intracarotid amobarbital injection. [1] Performance on each of these tests was rated on a four-point scale (unimpaired, mildly impaired, moderately impaired, and severely impaired). Language representation in the hemisphere ipsilateral to the side of injection was inferred if performance was at least mildly impaired on two tests with performance on another at least moderately impaired.…”
Section: Methodsmentioning
confidence: 99%
“…To assess laterality for language during this procedure, patients were given tests of reading, naming, repetition, and comprehension (in the form of a modified token test) after intracarotid amobarbital injection. [1] Performance on each of these tests was rated on a four-point scale (unimpaired, mildly impaired, moderately impaired, and severely impaired). Language representation in the hemisphere ipsilateral to the side of injection was inferred if performance was at least mildly impaired on two tests with performance on another at least moderately impaired.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors must still be considered in the interpretation of nonlateralizing IAP memory results. Among them is the effect of seizure focus side (left vs. right TLE), which is a frequent source of confusion in clinical practice (13,23). IAP memory scores tend to be lower after a dominant hemisphere injection than after a nondominant hemisphere anesthesia ( I 1,24), probably because of the deleterious effect on language function and consciousness (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus we can theoretically assume that the temporal lobe showing a poorer IAP memory result is the focus of a patient's TLE. Previous studies on the lateralizing value of IAP, however, have reported that IAP memory tests were frequently nonlateralizing (9)(10)(11)(12)(13). Wyllie et al (10) reported that the IAP correctly lateralized seizure focus in only 43% of TLE patients, and in 46%, the IAP memory test was indeterminate.…”
mentioning
confidence: 97%
“…Milner et al expanded the use of the Wada test to measure unilateral memory function in epilepsy surgery candidates in order to predict postoperative amnesia 12 . Since then, the contributions of the Wada test have been widely extended and include: (i) lateralisation of seizure focus [25][26][27][28][29][30][31][32] ; (ii) prediction of seizure control outcome 29,[33][34][35] ; and (iii) prediction of neuropsychological outcome [36][37][38][39][40][41] . On the other hand, its value to preclude postoperative amnesic syndromes still remains open to question 42,43 .…”
Section: The Wada Testmentioning
confidence: 99%